Two-stage supply chain contract coordination of solid biomass fuel involving multiple suppliers. (September 2019) - Fan, Kun; Li, Xinning; Wang, Lu; Wang, Meng
Highlights: Solid biomass fuels supply chain consists of multiple suppliers and one producer. The supply and demand of solid biomass fuels supply chain are both random. A combination of contracts can realize the coordination of the supply chain. The contracts can avoid the risk of the middleman's unjust increases in prices. Abstract: In the drive for energy structure optimization and sustainable development, the industrialization of biomass energy is undergoing constant improvements. The coordination of biomass solid fuel supply chain will improve both the profitability and efficiency for all participants. It will also promote the development of the biomass energy sector. In this paper, we take solid biomass fuel as the object, and build a supply chain model consisting of farmers, a middleman and a manufacturer. Farmers decide the supply to the manufacturer and the supply to the middleman. The middleman decides the supply to the manufacturer. The supply chain considers both random supply and stochastic demand due to random order times. Combining mathematical modeling with field research, we design a "protection price + subsidy" contract between farmers and the manufacturer, and a "buyback + revenue sharing" contract between the middleman and the manufacture that achieve the coordination of the supply chain. The research has solved the problem of insufficient supply of raw materials, and also avoided the risk of the middleman's unjust increase in price.